RANCANG BANGUN SISTEM INFORMASI DESA BANGKAL KECAMATAN BINANGUN BERBASIS WEB DAN MOBILE - Rafi Danish; Selfi Artika (Politeknik Bisnis Indonesia, 2023)
The rapid development of technology has had various negative and positive impact on humans, especially in the fields of communication and information. the positive impacts is the speed of the process delivering information via the internet such as websites, mobile applications and so on. For some people who are far from the city center, the process of obtaining and conveying information is still very limited, due to various internal and external factors. This research uses observation and interviews methods village officials and resident. Therefore, this website was created using PHP, Flutter Bootstrap, and MySQL Database with the aim of helping village communities obtain information services and assingting village goverment in providing information service facilities and being able to explore or introduce village culture and potential through web and mobile-based applications. The outcome of this study is an information system for villages in the form of a website and mobile that can manage village information, namely in the form of information services in the form of activites, news, galleries, correspondence services and this system can be accessed by anyone to get information about Bangkal village.